Teaching factory management during the Covid-19 pandemic - Yozi Vidiastuti; Nurtanio Agus Purwanto (ADGVI & Graduate School of Universitas Negeri Yogyakarta, 2021)
This research aims to determine how the teaching factory at SMK SMTI Yogyakarta handled during Covid-19 pandemic. A descriptive qualitative case study approach was used as the method. Semi-structured interview techniques, observation, and documentation were used to collect data. The interviewed data was collected from 3 informants. This study used triangulation techniques to check the validity of the data. The triangulation technique in this study used source triangulation, which compares the interview results of 3 informants to check the compatibility of the information obtained, then analyzed using an interactive model from Milles and Huberman. The implementation of the teaching factory at SMK SMTI Yogyakarta aims to improve student competence so that students can adapt and become accustomed to conditions in the real industrial world under the teaching factory's objectives. Schools continue to work with the industry on the implementation of the teaching factory in order to achieve the teaching factory's goals, and SOP (Standard Operational Procedures) are tailored to SOP from industries related to established health protocols. The implementation of the teaching factory can be done by forming a BLUD at the school level, which will form a learning process that is centered on entrepreneurship, with the income generated from the production used as capital, especially for SMK SMTI Yogyakarta.